2011
DOI: 10.1158/1078-0432.ccr-11-1048
|View full text |Cite
|
Sign up to set email alerts
|

Defective Mismatch Repair Status as a Prognostic Biomarker of Disease-Free Survival in Stage III Colon Cancer Patients Treated with Adjuvant FOLFOX Chemotherapy

Abstract: Purpose: Adding oxaliplatin to adjuvant 5-fluorouracil (5-FU) chemotherapy improves 3-year diseasefree survival (DFS) after resection of stage III colon cancer. Several studies suggest that patients with tumors exhibiting defective mismatch repair (MMR) do not benefit from adjuvant 5-FU chemotherapy, but there are few data on 5-FU-oxaliplatin (FOLFOX) adjuvant chemotherapy in this setting. The aim of this study was to evaluate the prognostic value of MMR status for DFS in patients with stage III colon cancer r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 37 publications
1
36
2
2
Order By: Relevance
“…Retrospective analyses of stage III colon cancer patients who received adjuvant FOLFOX suggest that dMMR CRCs maybe sensitive to oxaliplatin (49, 50); however, only limited data from prospective clinical trials evaluating oxaliplatin-based treatment are available (51, 50, 52). …”
Section: Treatmentmentioning
confidence: 99%
“…Retrospective analyses of stage III colon cancer patients who received adjuvant FOLFOX suggest that dMMR CRCs maybe sensitive to oxaliplatin (49, 50); however, only limited data from prospective clinical trials evaluating oxaliplatin-based treatment are available (51, 50, 52). …”
Section: Treatmentmentioning
confidence: 99%
“…To date, only limited data exist in MSI tumors from patients treated with oxaliplatin combined with 5-FU, and predictive information is lacking. A retrospective single-arm study in 5-FU plus oxaliplatin-treated stage III colon cancer patients found that the 3-year DFS rate was significantly higher in patients with deficient vs proficient MMR tumors (58), suggesting that the prognostic impact of MMR status is maintained since oxaliplatin is expected to provide equivalent benefit irrespective of MMR status.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Preclinical data indicate that MSI tumor cells are sensitive to oxaliplatin despite displaying resistance to 5-FU [33]. To date, however, data examining the prognostic/predictive impact of MMR on chemosensitivity to oxaliplatin-based treatment are very limited [34–37]. A preliminary clinical study suggested that the addition of oxaliplatin may reverse the 5-FU resistance for dMMR stage III colon cancer [35].…”
Section: Mmr Status and Clinical Outcome In Stage III Colon Cancermentioning
confidence: 99%